Sourcing the Arab Spring: A Case Study of Andy Carvin's Sources on Twitter during the Tunisian and Egyptian Revolutions. Issue 3 (1st April 2014) - Hermida, Alfred; Lewis, Seth C.; Zamith, Rodrigo
Abstract: News sourcing practices are critical as they shape from whom journalists get their information and what information they obtain, mostly from elite sources. This study evaluates whether social media platforms expand the range of actors involved in the news through a quantitative content analysis of the sources cited by NPR's Andy Carvin on Twitter during the Arab Spring. Results show that, on balance, nonelite sources had a greater representation in the content than elite sources. Alternative actors accounted for nearly half of the messages. The study points to the innovative forms of production that can emerge with new communication technologies, with the journalist as a central node trusted to authenticate and interpret news flows on social awareness streams.